Shree Gurudev Datta Highschool Website: A Digital Platform for Holistic Education and Growth - Maskar, Vidya; Mane, Sneha; Shinde, Sayali; Shitole, Siddhi; Patil, Kirti (International Journal of Computer Sciences and Engineering, 2024)
Creating a modern, user-friendly school website is crucial to improving communication and providing easy access to important resources for students, parents, and staff. This website will act as a central platform where the school’s values, academic programs, events, and achievements can be showcased. The goal is to ensure the website is easy to use, allowing users to navigate effortlessly through different sections. With a focus on intuitive design, the website will be optimized for mobile devices, ensuring that information is accessible on the go. Secure functionality will also be a priority to protect personal data and provide a safe online environment. Key interactive features, such as event calendars, announcements, and online admissions, will be integrated to enhance usability and engagement. By offering streamlined navigation and important tools at users’ fingertips, the website will reflect the school’s commitment to excellence in education and foster a stronger sense of community. It will serve as a dynamic resource for keeping everyone connected and informed.